The new European transport research activities - Kabashkin, Igor (Transport, 2004)
In the beginning of 2004 two European organisations – Organisation for Economic Co‐operation and Development (OECD) and European Committee of Ministers of Transport (ECMT), established the Joint OECD/ ECMT Transport Research Centre. The mission, main areas of research activities and projects of new European research centre are described. First Published Online: 27 Oct 2010